Differential Regulation of Protein Dynamics in Splanchnic and Skeletal Muscle Beds by Insulin and Amino Acids in Healthy Human Subjects - Nygren, Jonas; Nair, K. Sreekumaran (Diabetes (New York, N.Y.), 2003)
Differential Regulation of Protein Dynamics in Splanchnic and Skeletal Muscle Beds by Insulin and Amino Acids in Healthy Human Subjects Jonas Nygren and K. Sreekumaran Nair From the Division of Endocrinology, Mayo Clinic and Foundation, Rochester, Minnesota Abstract To determine the in vivo effect of amino acids (AAs) alone or in combination with insulin on splanchnic and muscle protein dynamics, we infused stable isotope tracers of AAs in 36 healthy subjects and sampled from femoral artery and vein and hepatic vein. The subjects were randomized into six groups and were studied at baseline and during infusions of saline (group 1), insulin (0.5 mU · kg −1 · min −1 ) (group 2), insulin plus replacement of AAs (group 3) insulin plus high-dose AAs (group 4), or somatostatin and baseline replacement doses of insulin, glucagon and GH plus high dose of AAs (group 5) or saline (group 6). Insulin reduced muscle release of AAs mainly by inhibition of protein breakdown. Insulin also enhanced AA-induced muscle protein synthesis (PS) and reduced leucine transamination. The main effect of AAs on muscle was the enhancement of PS. Insulin had no effect on protein dynamics or leucine transamination in splanchnic bed. However, AAs reduced protein breakdown and increased synthesis in splanchnic bed in a dose-dependent manner. AAs also enhanced leucine transamination in both splanchnic and muscle beds. Thus insulin’s anabolic effect was mostly on muscle, whereas AAs acted on muscle as well as on splanchnic bed. Insulin achieved anabolic effect in muscle by inhibition of protein breakdown, enhancing AA-induced PS, and reducing leucine transamination. AAs largely determined protein anabolism in splanchnic bed by stimulating PS and decreasing protein breakdown. Footnotes Address correspondence and reprint requests to K. Sreekumaran Nair, MD, Mayo Clinic and Foundation, Endocrine Research Unit, Joseph 5-194, 200 First St., S.W., Rochester, MN 55905. E-mail: nairatmayo.edu . Received for publication 10 July 2002 and accepted in revised form 7 March 2003. AA, amino acid; GC/MS, gas chromatography/mass spectrometry; KIC, ketoisocaproate; PB, protein breakdown; PS, protein synthesis. DIABETES